2013
DOI: 10.1200/jco.2011.40.1174
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Erlotinib Plus Concurrent Whole-Brain Radiation Therapy for Patients With Brain Metastases From Non–Small-Cell Lung Cancer

Abstract: A B S T R A C T PurposeBrain metastasis (BM) is a leading cause of death from non-small-cell lung cancer (NSCLC). Reasoning that activation of the epidermal growth factor receptor (EGFR) contributes to radiation resistance, we undertook a phase II trial of the EGFR inhibitor erlotinib with whole-brain radiation therapy (WBRT) in an attempt to extend survival time for patients with BM from NSCLC. Additional end points were radiologic response and safety. Patients and MethodsEligible patients had BM from NSCLC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
252
2
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(273 citation statements)
references
References 28 publications
(5 reference statements)
15
252
2
4
Order By: Relevance
“…Although RTOG 0320 found a potentially deleterious effect to combination SRS and erlotinib, Welsh et al found no significant additional neurotoxicity in a phase II study that added erlotinib to whole brain RT.The overall response rate was 86%. Compared with historic controls, patients had longer overall survival with combination therapy and patients with EGFR-mutant disease had particularly longer survival than those with EGFR wild-type disease [47,56]. Other agents of interest in lung cancer include the ALK mutation-targeted crizotinib, also approved for first-line treatment of ALK-positive lung cancer.…”
Section: Targeted Therapies For Breast Cancer Lung Cancer and Renalmentioning
confidence: 99%
“…Although RTOG 0320 found a potentially deleterious effect to combination SRS and erlotinib, Welsh et al found no significant additional neurotoxicity in a phase II study that added erlotinib to whole brain RT.The overall response rate was 86%. Compared with historic controls, patients had longer overall survival with combination therapy and patients with EGFR-mutant disease had particularly longer survival than those with EGFR wild-type disease [47,56]. Other agents of interest in lung cancer include the ALK mutation-targeted crizotinib, also approved for first-line treatment of ALK-positive lung cancer.…”
Section: Targeted Therapies For Breast Cancer Lung Cancer and Renalmentioning
confidence: 99%
“…Interestingly, patients negative for EGFR mutations had a median overall survival of 9.3 months, whereas patients who were positive for EGFR mutations had a median overall survival of 19.1 months. [89] The clinical benefit and feasibility of targeting ALK was demonstrated first with the multitargeted tyrosine kinase inhibitor crizotinib that competitively binds to the ATPbinding pocket of the ALK and MET tyrosine kinases and inhibits phosphorylation of activated ALK. This was subsequently confirmed in phase II and III trials.…”
Section: Breast Cancermentioning
confidence: 99%
“…Examples include PETbased approaches for noninvasive measuring of drug uptake with 89 Zr-trastuzumab and 89 Zr-bevacizumab. [106,107] Recent studies using magnetic resonance-guided focused ultrasound suggest a role for this noninvasive, radiationfree alternative for treatment of small deep-seated brain metastases.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Pre-clinical data showed a synergistic effect between EGFR-inhibition and radiotherapy (23), likely due to the radio-sensitizing effect of TKIs and to the damage of BBB caused by radiation. Different phase II studies demonstrated a tolerable safety profile and encouraging activity of WBRT and EGFR-TKI combination in EGFRpositive NSCLC patients with BM (24,25). The prospective randomized TRACTS study (NCT01763385) is currently investigating WBRT plus erlotinib combination vs. erlotinib alone in this subset of patients, and results are eagerly awaited.…”
mentioning
confidence: 99%